Antihypertensive antihyperlipidemicand antioxidantinfluence of D carvone in L NAME induced hypertensive rats - Raja, Boobalan (International Journal of Pharmaceutical & Biological Archive, 2015)
Antihypertensive antihyperlipidemicand antioxidantinfluence of D carvone in L NAME induced hypertensive rats